The Three Ages of Fuel Cell Research in France: A Socio‐Technical System's Resistance to Change1. Issue 3 (7th March 2014) - Belot, R.; Picard, F.; Steiner, Nadia; Hissel, Daniel; Bultel, Yann
Abstract As each emerging socio‐technological system, the fuel cell technology is characterized by hype and disappointment. This paper analyses from an historical perspective, the main events and the role of actors (policy makers, industrials, researchers) in this phenomenon in France from 1960 to 2010. It highlights three ages of fuel cell research. The emerging phase (from 1960 to 1980) is marked by the dominant role of the state and the weight of geopolitical considerations supporting research growth. From 1980 to 1990, a withdrawal phase is explained by the limited prospects for industrial application, the weakening of the state's strategic role and the balance of power within the academic world. In 1990s, the renewal phase seems to come from manufacturers and the European Union, the French state being content to support the process from the side‐line.